Exploring the potential of lignin extracted with natural deep eutectic solvents for adsorption of carbon dioxide - Meraj, Aatikah; Jawaid, M.; Nasef, Mohamed Mahmoud; Mohamad, Noor Ashikin; Singh, Surendra Pratap; Ariffin, Hidayah; Abu‐Jdayil, Basim (Springer Science and Business Media Deutschland GmbH, 2024)
The utilization of natural deep eutectic solvents in the extraction of lignin presents a promising sustainable approach for biorefineries. While lignin extracted with NADES has been utilized in various applications, there is a lack of research on its potential for CO2 adsorption. This article aims to assess the potential of CO2 adsorption on lignin extracted with NADES. In this work, lignin was studied, and their properties were analyzed using analytical techniques such as FTIR, XRD, TGA, SEM, BET, and particle size analysis. The gravimetric adsorption method was employed to evaluate the CO2 adsorption capacity of lignin. Thermal analysis showed broader decomposition at 416.45 °C, suggesting potential suitability for exploration of CO2 adsorption. The lignin exhibited high selectivity towards CO2 at an adsorption capacity of 75 mg/g at 30 bar. Lignin exhibited Type-II adsorption isotherm which indicates existence of multilayer adsorption. CO2 adsorption performance agrees well with BET and SEM results, revealing low surface area in the NADES extracted lignin and dense-like structure. It also showed good stability after 10 adsorption/desorption cycles. The overall results of this study suggests that the lignin extracted with NADES has the potential for application in CO2 adsorption that requires further exploration.